The contribution of memory to differences in situation awareness in expert and non-expert drivers. (October 2021) - Pammer, Kristen; McKerral, Angus; Liu, Yu
Highlights: Expert drivers offer valuable insights into trainable, driving-related constructs. We investigated if expert driver's SA for driving may be explained by superior memory. Expert drivers had better SA for most categories, compared with non-expert drivers. SA was not due to short-term visual, phonological or long-term memory processes. SA was also not explained by other driving-related demographic variables. We also developed a new driving-related SA, which may be developed in future research. Abstract: Situation awareness (SA) is knowing what is going on in the environment: identifying objects, understanding how they interact and predicting future events. It is important in the context of driving as it is related to hazard perception. Driving-related SA may help explain expert drivers' superior driving skill, but it is important to understand whether this is because expert drivers have better memory for driving-related tasks, whether superior memory performance is task specific, and the degree to which any effect is attributable to experience vs. expertise. On-road paramedics were compared with non-expert drivers. The participants engaged in an SA driving task where they were required to describe a vide taped driving situation after the screen cut to black. We measured their SA, memory and demographic driving variables. The starting SA of World, Action and Schema was re-developed to better reflect driving SA, into World, Action, Other-Agent Action, Projection, and Rationale. Driving expertise predicted each category of SA, except the Action category, independently of other experience variables. Similarly, expertise also predicted SA categories independently of any of the memory tasks. We concluded that expert drivers have better driving-SA than non-expert drivers and this is not due to better memory for driving tasks, or 'time-on-road'. This finding is important in driver training because if we can harness the SA skills that expert drivers demonstrate, we could potentially implement them in better driver training programs.